Implementasi Game Edukasi Sebagai Media Pembelajaran Pengembangan Kemampuan Kognitif Berbasis Power Point Di TK Aisyiyah Semanggi - Winda Nur Ayu Afifaroh; Aulina Tiadivti Rahma Fitra; Annissa Ludfianti; Alya Khusnul Qotimah (Academica: Journal of Multidisciplinary Studies, 2023)
Introduction to the concept of mathematics is a form learning that falls within the realm of a child’s cognitive development. Cognitive is one aspect of child development that needs to be stimulated with good to develop optimally. Games can be used as an alternative in stimulating the introduction of mathematical concept in children so that not only glued with stimulants in the form of sheets of paper only children’s work. This research aims to apply power point based educational games to development of early childhood cognitive abilities. Characteristic on game educative that will be tested is fun, motivating and entertaining. As for this study is a study that uses qualitative methods with subject phenomenology researcher is student of class B TK Aisyiyah IV Semanggi. Observation and interview result show the children that can complete the game development of cognitive abilities well and more fun for son. From the results of the study can be concluded that educational games power point based feasible use in stimulating cognitive child.